2008
DOI: 10.1021/ic8011074
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Magnetic Anomalies in Solvates of the Bis(hexafluoroacetylacetonate)copper(II) Complex with Pyrazolyl-Substituted Nitronyl Nitroxide

Abstract: We succeeded in synthesizing of a whole family of isostructural solvates of the copper(II) hexafluoroacetylacetonate complex with pyrazolyl-substituted nitronyl nitroxide (L): Cu(hfac)2L x 0.Solv. The main feature inherent in nature of Cu(hfac)2L x 0.5 Solv single crystals is their incredible mechanical stability and ability to undergo reversible structural rearrangements with temperature variation, accompanied by anomalies on the mu(eff(T)) dependence. Structural investigation of the complexes over a wide tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 44 publications
4
97
0
Order By: Relevance
“…It was shown that a mild modification of T c for [Cu(hfac) 2 L n-Bu ]·0.5solv required a considerably smaller structural step than one methylene unit in the homologous series, typical in organic chemistry. 50 Figure 9.3 illustrates the important circumstance that the packing mode of polymer units is the same in solid solvates with hexane, heptane, octane, and octene, which is confirmed by the form of chains in both perpendicular and axial directions as shown in Figure 9 This can readily be seen, for example, if we compare the μ eff (T) dependences for the solvate with hexane ( Fig. 9.2d) and the solvate with octane ( Fig.…”
Section: Relationship Between the Chemical Step And The Physical Propmentioning
confidence: 62%
See 2 more Smart Citations
“…It was shown that a mild modification of T c for [Cu(hfac) 2 L n-Bu ]·0.5solv required a considerably smaller structural step than one methylene unit in the homologous series, typical in organic chemistry. 50 Figure 9.3 illustrates the important circumstance that the packing mode of polymer units is the same in solid solvates with hexane, heptane, octane, and octene, which is confirmed by the form of chains in both perpendicular and axial directions as shown in Figure 9 This can readily be seen, for example, if we compare the μ eff (T) dependences for the solvate with hexane ( Fig. 9.2d) and the solvate with octane ( Fig.…”
Section: Relationship Between the Chemical Step And The Physical Propmentioning
confidence: 62%
“…50 For [Cu(hfac) 2 L n-Bu ]·0.5C 5 H 11 I, the structural characteristics at lowered temperatures are quite different, the dominant tendency being the lengthening of the Cu-O L bond after the transition. Therefore, the abrupt change in μ eff and the character of μ eff (T) are different for this compound ( Fig.…”
Section: Relationship Between the Chemical Step And The Physical Propmentioning
confidence: 99%
See 1 more Smart Citation
“…Inaccuracy of this basis for these systems was previously demonstrated in Ref. 13 on some other compounds of "breathing crystal" family. Table II of effective magnetization versus temperature.…”
Section: B the Cu(hfac) 2 L Et Casementioning
confidence: 83%
“…12 DFT calculations of the magnetic coupling constant in a three-spin cluster of crystal unit cell were previously published by Gorelik et al 13 and Zueva et al 14 In the former work PBE0 hybrid exchange-correlation functional with 6-31G(d) basis set were used, and the results have shown some limitations of the approach to describe the magnetic coupling in exchange clusters of the "breathing crystals" near the transition temperature. In Ref.…”
Section: -mentioning
confidence: 99%